Rassal yürüyüşe deneysel bir yaklaşım - Alan, Murat (My University, 1999)
In the stock market, which importance increases day by day in the capital market the investors uses some approved analysis methods to determine their direction and so increase their earnings. In the other side not only stocks but also the market of stock must be well-analized and dynamics of them must be determined. The basic analysis, technical analysis and random walk concepts are result of these investigations. Random walk, in Turkish rassal yürüyüş hipotezi says that short-term changes at the price of the stocks could not be known before and the price of the stocks could not be estimated only using the past returns and trend of its. Its required that the concepts of Market Efficiency, Efficient Market Theory, Portfolio Theory and Capital Asset Pricing Model must be investigated to test the meaning and the currency of the random walk theory in the market. According to reflection ratio of information on prices market efficiency can be examined at three category as weak, semi-strong and strong efficient markets. In efficient market there is three information group that determine the stock price; 1- Informations related to past prices and return of stock, 2- All public informations of stock, 3- Special informations of stock. Semi-strong efficient markets are the markets that all the public informations are reflected absolutely on the present value of the stock prises. The theory defends that the stock prices includes all the public and special informations about the stock. Weak efficient market theory defends that to use trend of stocks are unimportant to determine the future prices of stocks because all the past informations are included in the stocks prices. 65 According to random walk theory; a stock's future prices cannot be estimated as the behaviour of cumulatif random numbers series. Consecutive price variations are not completely independent but real dependency degree is so small that it can be neglected. In a free competitive market; the price of a special product or service must be include all informations that interest participants. All future conditions relating to supply and request are known so effect of these conditions on the present prices must be take into consideration. Technical analysis is an analysis that determine the price changes and observe trends of stock prices to determine the future characteristics and trends of stocks. Technical analysis defends that prices follow trends. In a weak efficient market, technical analysis method can be succesful only by chance. Because the prices are occured by the different evaluation of the information that come to the market randomly so the price changes are show random characteristic. On other side there is no opposition between the random walk theory and basic analysis method that says The price of a capital asset is a function of the company's financial structure. Random walk theory doesn't say anything about long-term periods, it says in a short-term periods distributions of the stock prices around the actual value can be occured by chance. In a weak efficient market the price variations are arise according to random walk theory. Because in a weak efficient market the price variations are completely random and independent. So the validity of weak efficient market theory is also guarantee the validity of random walk theory. Many of researchers have used regression analysis, run test and filter rule test that known as a random walk tests to determine the currency of the weak efficient market theory. Other than these mentioned test above there are some test that are applied to test the validity of random walk and weak efficient market theories but here only these two mentioned analysis methods are used for this purpose. 66 In this study, the corrected stock prices and montly income of 25 İMKB-100 companies between 1992 January and 1997 December are used for analysis. These corrected values are the recent values that İMKB Statistical and Planning Department registered. In this study, monthly prices and monthly interests are used seperatly to test the random walk theory and these result are compared. For the monthly prices and interests series, it is analysed that is there any long-term trends. As a result of the regression analysis and run test techniques, it can be say that for short term periods there is a dependency between the stock prices but for long term periods there is no such relation between their prices. This positif relation between the prices that arise in short term periods can not be used for over income. Because this impact are destroyed by the treatment commission. On the other side, the random walk theory defends that the distribution around the actual value can be occured by chance. So some short term trends that arise at the result of analysis don't conflict with the random walk theory. So the random walk theory is valid in general, in other word the prices don't follow a trend, oppositely the price variations are distributed randomly.
Keywords: Bankalar ve Bankacılık